2020
DOI: 10.1101/2020.06.14.151357
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Spike D614G mutation increases SARS-CoV-2 infection of multiple human cell types

Abstract: AbstractA novel isolate of the SARS-CoV-2 virus carrying a point mutation in the Spike protein (D614G) has recently emerged and rapidly surpassed others in prevalence. This mutation is in linkage disequilibrium with an ORF1b protein variant (P314L), making it difficult to discern the functional significance of the Spike D614G mutation from population genetics alone. Here, we perform site-directed mutagenesis to introduce the D614G variant and show that in multiple cell lines, i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
199
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(215 citation statements)
references
References 23 publications
10
199
5
1
Order By: Relevance
“…Although virions produced from Calu-3 cells had more complete S1/S2 cleavage than those produced form Vero E6 cells, no substantial differences in spike cleavage were detectable between the D614 and G614 virions produced from either cell type, suggesting that the enhanced virion infectivity is not likely due to the D614G-mediated spike cleavage difference. Our results from authentic SARS-CoV-2 are in contrast with previous studies reporting that the D614G mutation changes the cleavage and shedding of spike protein when expressed alone or in the context of pseudotyped virions 24,25 . Mechanistically, two recent studies showed that the D614G mutation abolishes a hydrogen-bond interaction with T859 from a neighboring protomer of the spike trimer 6 , which allosterically promotes the RDB domain to an "up" conformation for receptor ACE2 binding and fusion 7 , leading to an enhanced virion infectivity.…”
Section: Discussioncontrasting
confidence: 99%
“…Although virions produced from Calu-3 cells had more complete S1/S2 cleavage than those produced form Vero E6 cells, no substantial differences in spike cleavage were detectable between the D614 and G614 virions produced from either cell type, suggesting that the enhanced virion infectivity is not likely due to the D614G-mediated spike cleavage difference. Our results from authentic SARS-CoV-2 are in contrast with previous studies reporting that the D614G mutation changes the cleavage and shedding of spike protein when expressed alone or in the context of pseudotyped virions 24,25 . Mechanistically, two recent studies showed that the D614G mutation abolishes a hydrogen-bond interaction with T859 from a neighboring protomer of the spike trimer 6 , which allosterically promotes the RDB domain to an "up" conformation for receptor ACE2 binding and fusion 7 , leading to an enhanced virion infectivity.…”
Section: Discussioncontrasting
confidence: 99%
“…The subunit S2 has a fusion peptide (788 to 806), a heptad repeat 1 (912-984), a heptad repeat 2 (1163-1213), a transmembrane domain (1213-1237) and a cytoplasmic tail (1238-1273) 47 . As reported in the earlier studies [48][49][50][51] D614G (present in the S1 subunit flanked by the receptor binding site) (Figure 4) mutation is found to be highly significant and present at 75% rate in the second phase. Together in both the phases, 68 countries (except 16 countries, namely, Brunei, Sweden, Panama, Cambodia, Tunisia, Malaysia, Nepal, South Korea, Philippines, Iran, Pakistan, Ghana, Uruguay, Qatar, Bangladesh and Guam) have this mutation (Figure 2(B)).…”
Section: D614g and D936y Are The Prominent Mutations In The Spike Prosupporting
confidence: 83%
“…Recently, several groups also reported that S-G614 enhances viral infectivity based on pseudovirus assays [23][24][25][26] , but due to the small sample size, they found no effect on the neutralization sensitivity of the virus 23,24,26 . Given the evolving nature of the SARS-CoV-2 RNA genome, antibody treatment and vaccine design require further considerations to accommodate D614G and other mutations that may affect the immunogenicity of the virus.…”
Section: Discussionmentioning
confidence: 99%